A combinatorial screening protocol for identifying novel and highly potent dual-target inhibitor of BRD4 and STAT3 for kidney cancer therapy - Zhang, Shizhu; Wu, Nan; Geng, Yifei; Guan, Lixia; Niu, Miao-Miao; Li, Jindong; Zhu, Lusha (Frontiers in Pharmacology, 2025)
Concurrent inhibition of bromodomain-containing protein 4 (BRD4) and signal transductor and activator of transcription 3 (STAT3) could potentially be an effective strategy against renal cell carcinoma (RCC). Here, we successfully identified five dual-targeted BRD4/STAT3 inhibitors (BSTs 1–5) using a combinatorial screening protocol. Particularly, BST-4 was the most potent inhibitor simultaneously targeting BRD4 (IC50 = 2.45 ± 0.11 nM) and STAT3 (IC50 = 8.07 ± 0.51 nM). MD simulation indicated that BST-4 stably bound to the active sites of BRD4 and STAT3. The cytotoxicity assays exhibited that BST-4 had a significant antiproliferative activity against RCC cell lines, especially CAKI-2 cells (IC50 = 0.76 ± 0.05 μM). Moreover, in vivo experiments revealed that BST-4 more effectively inhibited the growth of xenograft tumors compared with positive controls RVX-208 and CJ-1383. Overall, these data indicated that BST-4 could be a promising candidate compound for RCC therapy.